1973
DOI: 10.1007/bf01230687
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an ??-amylase inhibitor (BAY d 7791) on blood glucose, serum insulin and nefa in starch loading tests in rats, dogs and man

Abstract: An a-amylase inhibitor isolated from wheat was used in experiments involving rats, dogs and healthy volunteers. The hyperglycaemia and hyperinsulinaemia resulting from starch loading could be reduced dose dependently by the inhibitor. Its inhibitory effect is specific and limited to s-amylase. In loading tests with cooked starch the effect on blood sugar is markedly diminished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(51 citation statements)
references
References 6 publications
(2 reference statements)
5
46
0
Order By: Relevance
“…Recently comparison of a range of carbohydrate foods [37] and foods processed in different ways [38] have indicated that the glycaemic response may be predicted from the rate at which a food is digested in vitro. In turn the digestibility of foods has been shown to be reduced by the presence of enzyme inhibitors [39], lectins [40] and phytates [41], all of which are contained in beans. In vitro studies of cooked legumes have indeed shown that these are digested less rapidly than other carbohydrate foods [37,42].…”
Section: Discussionmentioning
confidence: 99%
“…Recently comparison of a range of carbohydrate foods [37] and foods processed in different ways [38] have indicated that the glycaemic response may be predicted from the rate at which a food is digested in vitro. In turn the digestibility of foods has been shown to be reduced by the presence of enzyme inhibitors [39], lectins [40] and phytates [41], all of which are contained in beans. In vitro studies of cooked legumes have indeed shown that these are digested less rapidly than other carbohydrate foods [37,42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, according to the recent estimates, the human population worldwide appears to be in the midst of an epidemic of diabetes mellitus, a metabolic disorder characterized by chronic hyperglycaemia. Retardation of the digestion of starch by key gastrointestinal enzymes can be of benefit to the diabetic patients (Puls and Keup, 1973). Since glucose release from food sources is the main factor affecting post-prandial hyperglycaemia, the use of á-amylase inhibitors is essential to control it.…”
Section: Introductionmentioning
confidence: 99%
“…Various flavonoids and non-flavonoids have been reported as showing radical scavenging activity (Sawa et al, 1999): flavone, and flavonoids inhibit α-amylase and α-glucosidase activities (Havsteen, 1983;Kim et al, 2000); polyphenols have anti-hyperglycemic effects (Hossain et al, 2002;Hanamura et al, 2006), and inhibit the development of diabetes (Zunimo et al, 2007). Since glucose release from food sources is the main factor affecting post-prandial hyperglycaemia, retardation of the digestion of starch by key gastrointestinal enzymes can be of benefit to diabetic patients (Puls and Keup, 1973). Also, various dietary components such as polyphenols in tea (Matsuo et al, 2000), soybean (Takasugi et al, 2002), and apple (Kanda et al, 1998), fla-vonoids (Corvazier and Maclouf, 1985), and polyunsaturated fatty acids (Yamada et al, 1996) suppress the release of mediators from basophils or mast cells, which in turn prevent the pathogenesis of type 1 allergy.…”
Section: Introductionmentioning
confidence: 99%